New records of Astyanax pelegrini Eigenmann, 1907 and Triportheus pantanensis Malabarba, 2004 (Actinopterygii: Characiformes: Characidae) for the Río Pilcomayo National Park and Ramsar Site in the province of Formosa, Argentina - Brancolini, Florencia (2011)
This note presents the first records of Astyanax pelegrini Eigenmann, 1907 and Triportheus pantanensis Malabarba, 2004 for the province of Formosa, Argentina from fish surveys conducted in the Río Pilcomayo National Park and Ramsar Site. In the case of T. pantanensis, this occurrence represents the first record of this species for Argentina.